Presentation, management, and outcomes of 25 748 acute coronary syndrome admissions in Kerala, India: results from the Kerala ACS Registry - Mohanan, Padinhare Purayil; Mathew, Rony; Harikrishnan, Sadasivan; Krishnan, Mangalath Narayanan; Zachariah, Geevar; Joseph, Jhony; Eapen, Koshy; Abraham, Mathew; Menon, Jaideep; Thomas, Manoj; Jacob, Sonny; Huffman, Mark D; et al. (European heart journal, 2013)
There are limited contemporary data on the presentation, management, and outcomes of acute coronary syndrome (ACS) admissions in India. We aimed to develop a prospective registry to address treatment and health systems gaps in the management of ACSs in Kerala, India. We prospectively collected data on 25 748 consecutive ACS admissions from 2007 to 2009 in 125 hospitals in Kerala. We evaluated data on presentation, management, and in-hospital mortality and major adverse cardiovascular events (MACE). We created random-effects multivariate regression models to evaluate predictors of outcomes while accounting for confounders. Mean (SD) age at presentation was 60 (12) years and did not differ among ACS types [ST-segment myocardial infarction (STEMI) = 37%; non-STEMI = 31%; unstable angina = 32%]. In-hospital anti-platelet use was high (>90%). Thrombolytics were used in 41% of STEMI, 19% of non-STEMI, and 11% of unstable angina admissions. Percutaneous coronary intervention rates were marginally higher in STEMI admissions. Discharge medication rates were variable and generally suboptimal (<80%). In-hospital mortality and MACE rates were highest for STEMI (8.2 and 10.3%, respectively). After adjustment, STEMI diagnosis (vs. unstable angina) [odds ratio (OR) (95% confidence interval = 4.06 (2.36, 7.00)], symptom-to-door time >6 h [OR = 2.29 (1.73, 3.02)], and inappropriate use of thrombolysis [OR = 1.33 (0.92, 1.91)] were associated with higher risk of in-hospital mortality and door-to-needle time <30 min [OR = 0.44 (0.27, 0.72)] was associated with lower mortality. Similar trends were seen for risk of MACE. These data represent the largest ACS registry in India and demonstrate opportunities for improving ACS care.